Targeting ACLY Attenuates Tumor Growth and Acquired Cisplatin Resistance in Ovarian Cancer by Inhibiting the PI3K–AKT Pathway and Activating the AMPK–ROS Pathway - Wei, Xuan; Shi, Juanjuan; Lin, Qianhan; Ma, Xiaoxue; Pang, Yingxin; Mao, Hongluan; Li, Rui; Lu, Wei; Wang, Yu; Liu, Peishu (Frontiers in Oncology, 2021)
Abstract Background: Ovarian cancer is the most lethal female genital malignancy. Although cisplatin is the first-line chemotherapy to treat ovarian cancer patients along with debulking surgeries, its efficacy is limited due to the high incidence of cisplatin resistance. ATP citrate lyase (ACLY) has been shown to be a key metabolic enzyme and is associated with poor prognosis in various cancers, including ovarian cancer. Nevertheless, no studies have probed the mechanistic relationship between ACLY and cisplatin resistance. Methods: Survival analysis was mainly carried out online. Bioinformatic analysis was performed in R/R studio. Proliferative activity was measured by MTT and colony formation assays. Cell cycle and apoptosis analysis were performed by flow cytometry. The acquired-cisplatin-resistant cell line A2780/CDDP was generated by exposing A2780 to cisplatin at gradually elevated concentrations. MTT assay was used to calculate IC50 values of cisplatin. A xenograft tumor assay was used test cell proliferation in vivo. Results: Higher expression of ACLY was found in ovarian cancer tissue and related to poor prognosis. Knockdown of ACLY in A2780, SKOV3, and HEY cells inhibited cell proliferation, caused cell-cycle arrest by modulating the P16–CDK4–CCND1 pathway, and induced apoptosis probably by inhibiting p-AKT activity. Bioinformatic analysis of the GSE15709 dataset revealed upregulation of ACLY and activation of PI3K–AKT pathway in cells with acquired cisplatin resistance, in line with observations on A2780/CDDP cells that we generated. Knockdown of ACLY alleviated cisplatin resistance, and works synergistically with cisplatin treatment to induce apoptosis in A2780/CDDP cells by inhibiting the PI3K–AKT pathway and activating AMPK–ROS pathway. The ACLY-specific inhibitor SB-204990 showed the same effect. In A2780/CDDP cells, AKT overexpression could attenuate cisplatin re-sensitization caused by ACLY knockdown. Conclusions: Knockdown of ACLY attenuated cisplatin resistance by inhibiting the PI3K–AKT pathway and activating the AMPK–ROS pathway. These findings suggest that a combination of ACLY inhibition and cisplatin might be an effective strategy for overcoming cisplatin resistance in ovarian cancer.